Vật liệu aluminosilicat mao quản trung bình từ cao lanh. Phần 1. Tổng hợp và đặc trưng vật liệu aluminosilicat mao quản trung bình MSU-S có cấu trúc zeolit Y trong môi trường kiềm - Hảo, Phạm Minh; Đôn, Tạ Ngọc; Yêm, Hoàng Trọng (Vietnam Journal of Chemistry, 2014)
Mesostructured aluminosilicate and composite of mesostructured aluminosilicate with NaY zeolite crystals assembled from faujasitic (FAU) zeolite seeds were synthesized successfully from metakaolin in the presentation of cetyltrimethylamoniumbromua (CTAB)  C16H33N(CH3)3Br. The materials were characterized by XRD, nitrogen adsorption isotherm BET, TEM, SEM, IR, TPD-NH3vµ TGA-DSC. The results exhibited hexagonal mesostructure containing FAU zeolite seeds on the walls having a thickness of approximately 1.0 nm, pore size of 3.8 nm, the BET surface area of 782 m2/g and 720 m2/g, respectively, thermal stability until 700oC. These materials contain both strong and medium acidic sites. They have potential applications in adsorption and catalysis.